Ergonomic Tool Design Must Be in Accordance with the Anthropometric Dimensions of the User's Workforce - Gempur Santoso (Journal of Innovation Research and Knowledge, 2026)
Abstrak: If a tool is not suitable for the user and is forced, the user will become tired easily and productivity will not be good. Ergonomic tools are devices specifically designed to adapt to the abilities, limitations, and dimensions of the body. This article is designed descriptively, namely it will be compared and explained. All data in this article is derived from expert opinions and research findings, commonly referred to as literature studies. Furthermore, the analysis also uses descriptive methods. Conclusion: that in designing work equipment it is best to know the work position, then the employee's anthropometric data as equipment size data, and finally it can reduce fatigue and improve work productivity. Suggestion: companies should design work equipment that is adapted to the anthropometry of employees so that it is ergonomic.